The pain of the subalterns and the desire for an unfinished revolution: Narratives about political violence in the Aymara Nation – Peru - Jesús Wiliam Huanca-Arohuanca (2020)
In the lines that come, as a target macro, attempts will be made to examine the political violence and claims of revolution by the actors of the Aymara Nation (NAM) as it encounters a profound impact caused by the seditious groups and the Peruvian state in the context of the dark decade of the 80s and 90s of the last century that remains a sequel to the collective memory of the victims. Considering the qualitative approach, in-depth interview and discourse analysis as a fundamental hermeneutic orientation, the perceptions of the 12 actors who were leaders in the fabric of violence are examined. The results show that the violation of Human Rights (HR) under repression, persecution and selective disappearances to the detriment of the Aymara population, creates tensions, fear, paranoia and the desire of revolution against insurgent groups and the same State that was once complicit in the genocide to the heart of the inhabitants of the NAM. In conclusion, only the opening of binding democratic channels between government and Aymara can redefine new spaces for transdisciplinary dialogues guarded by truth and imperative justice.